A comparison of a novel robust decentralised control strategy and MPC for industrial high purity, high recovery, multicomponent distillation. (July 2017) - Udugama, Isuru A.; Wolfenstetter, Florian; Kirkpatrick, Robert; Yu, Wei; Young, Brent R.
Abstract: In this work we have developed a novel, robust practical control structure to regulate an industrial methanol distillation column. This proposed control scheme is based on a override control framework and can manage a non-key trace ethanol product impurity specification while maintaining high product recovery. For comparison purposes, a MPC with a discrete process model (based on step tests) was also developed and tested. The results from process disturbance testing shows that, both the MPC and the proposed controller were capable of maintaining both the trace level ethanol specification in the distillate ( X D ) and high product recovery ( β ). Closer analysis revealed that the MPC controller has a tighter X D control, while the proposed controller was tighter in β control. The tight X D control allowed the MPC to operate at a higher X D set point (closer to the 10 ppm AA grade methanol standard), allowing for savings in energy usage. Despite the energy savings of the MPC, the proposed control scheme has lower installation and running costs. An economic analysis revealed a multitude of other external economic and plant design factors, that should be considered when making a decision between the two controllers. In general, we found relatively high energy costs favour MPC. Abstract : Highlights: An industrial methanol distillation column with a side draw was modelled. A Novel Control scheme based on override control was proposed to control both the product purity and recovery. The control scheme was compared with a MPC structure. Both control schemes achieve on specification operations and performs similarly. Economic analysis showed that the novel control scheme would be preferred for low to medium energy prices.